1994
DOI: 10.1523/jneurosci.14-08-04639.1994
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in glial-derived factors that promote dendritic outgrowth from mouse cortical neurons in vitro

Abstract: To determine whether glia from different CNS regions differ in their ability to support axons or dendrites, embryonic (E18) mouse cortical neurons were cocultured with early postnatal (P4) rat astroglial derived from cortex, retina, olfactory bulb, mesencephalon, striatum, and spinal cord. After 5 d in vitro, axon and dendrite outgrowth from isolated neurons was quantified with double-labeling immunohistochemical techniques. Whereas axonal growth was similar on the various monolayers, total primary dendritic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 67 publications
2
49
0
1
Order By: Relevance
“…In our experiment, we have not discriminated between axonal and dendritic growth. Thus, our results are not at variance with those of Chamak et al (1987) and Qian et al (1992) who reported that axonal growth was more stimulated in heterotopic cocultures, whereas Le Roux and Reh (1994) reported that dendritic growth was increased in homotopic cocultures. Finally, we observed that a CM from ϩ/ϩ or double KO astrocyte cultures did not increase neurite growth.…”
Section: Is the Absence Of Gfap Linked To A Higher Neuronal Survival supporting
confidence: 54%
“…In our experiment, we have not discriminated between axonal and dendritic growth. Thus, our results are not at variance with those of Chamak et al (1987) and Qian et al (1992) who reported that axonal growth was more stimulated in heterotopic cocultures, whereas Le Roux and Reh (1994) reported that dendritic growth was increased in homotopic cocultures. Finally, we observed that a CM from ϩ/ϩ or double KO astrocyte cultures did not increase neurite growth.…”
Section: Is the Absence Of Gfap Linked To A Higher Neuronal Survival supporting
confidence: 54%
“…Previous work has demonstrated that glial cells derived from different regions of the CNS are heterogeneous in their abilities to support dendritic growth from mouse cortical neurons in vitro (Denis-Donini et al, 1984;Chamak et al, 1987;Autillo-Touati et al, 1988;Rousselet et al, 1988Rousselet et al, , 1990Prochiantz et al, 1990;Le Roux and Reh, 1994). The results from the experiments described in this report demonstrate that this difference is due to differential maintenance of primary dendrite number, rather than differences in the ability of various glia to induce the initiation of dendntic processes.…”
Section: Discussionmentioning
confidence: 55%
“…In a previous study we have found that soluble factors are responsible for the different capacities of glia to support dendrite number (Le Roux and Reh, 1994). Therefore, in the present study we plated El 8 mouse cortical neurons at low density (1 X 1 O4 cells/ml) directly onto polylysine coverslips for 24 h in conditioned media from either mesencephalic glia or cortical glia and, after 24 h in vitro, exchanged the media so that cortical neurons initially exposed to cortical glia were now grown in media conditioned by mesencephalic glia, whereas cortical neurons first exposed to mesencephalic glia were now exposed to cortical glia.…”
Section: Glia Are Necessary To Maintain the Primary Dendritic Arbormentioning
confidence: 97%
“…Furthermore, the basis for such a proposal would imply that classical stellate astroglia represent a rather uniform -structurally and chemically -cell type, associated among their constituents in a sort of panglial syncytium (according to current concepts on cerebral cortex astroglial architecture), or rather, syncytial-like (Mugnaini, 1986). Yet, such astroglial cell uniformity is no longer a tenable assumption, as it has been demonstrated during recent years to express multiple cell types and brain regional differences, as they are able to generate and receive chemical signals, thus participating in neurono:glial intercellular signaling and brain circuit organization and function (Araque et al, 1999;Hertz, 1965;Le Roux and Reh, 1994;Monard et al, 1973;Nedergaard, 1994;Pfrieger, 2002;Retzius, 1894;Tsacopoulos and Magistretti, 1996;Ullian et al, 2001). These dynamic functions go beyond a role restricted to management of the extracellular space composition and that one based on a 'mass' effect.…”
Section: Einstein's Cerebral Cortex Analysismentioning
confidence: 99%